Outcomes of transcatheter device closure in atrial septal defect secundum in Kelantan : a single center experience - Niza@Nizal, Hanif Mohd @Mohd (2018)
Background – To look at demographic, procedural and clinical characteristic of patients with atrial septal defect secundum (ASDs) who underwent transcatheter device closure, median survival time to ASDs closure and its outcome in pediatric and adult patients. Material and methods – This retrospective study was conducted from January 2005 to December 2015 in patients with ASDs underwent transcatheter device closure at Hospital Universiti Sains Malaysia. Results – 73 patients (42 children and 31 adults) with 75% of female predominance. Median age at diagnosis was 8 years old and median age at procedure was 15 years old. 25% of patients are symptomatic on procedural day, with reduced effort tolerance being the most reported symptoms (83%). Majority of patients had large ASDs, with median of 22mm (7mm – 33.6mm), with 60% of patients had rim deficiency. Median survival time of ASDs closure in pediatric and adult age group were 3 years and 2 years respectively. Success rate was 90.4%. There was 5.5% residual shunt immediately after procedure, with 100% complete resolution at the end of follow-up at 2 years. Conclusions – Transcatheter device closure is safe and effective in large ASDs population with rim deficiency, with comparable outcome and minimal serious complication.